Weak interactions modulating the dimensionality in supramolecular architectures in three new nickel(II)-hydrazone complexes, magnetostructural correlation, and catalytic potential for epoxidation of alkenes under phase transfer conditions - Sadhukhan, Dipali (2011)
Three different ONO donor acetyl hydrazone Schiff bases have been synthesized from the condensation of acetic hydrazide with three different carbonyl compounds: salicylaldehyde (HL 1), 2-hydroxyacetophenone (HL 2), and 2, 3-dihydroxybenzaldehyde (HL 3). These tridentate ligands are reacted with Ni(OOCCF 3) 2· xH 2O to yield three new Ni(II) complexes having distorted octahedral geometry at each Ni center: [Ni(L 1)(OOCCF 3)(CH 3OH)] 2 (1), [Ni(L 2)(OOCCF 3)(H 2O)] 2 (2), and [Ni(L 3)(L 3H)] (OOCCF 3)(H 2O) 1.65(CH 3OH) 0.35 (3). The ligands and the complexes have been characterized by elemental analysis and IR and UV-vis spectroscopy, and the structures of the complexes have been established by single crystal X-ray diffraction (XRD) study. 1 and 2 are centrosymmetric dinuclear complexes and are structural isomers whereas 3 is a bis chelated cationic monomer coordinated by one neutral and one monoanionic ligand. O-H⋯O hydrogen bonds in 3 lead to the formation of a dimer. Slight steric and electronic modifications in the ligand backbone provoke differences in the supramolecular architectures of the complexes, leading to a variety of one, two, and three-dimensional hydrogen bonded networks in complexes 1-3 respectively. Variable temperature magnetic susceptibility measurements reveal that moderate antiferromagnetic interactions operate between phenoxo bridged Ni(II) dimers in 1 and 2 whereas very weak antiferromagnetic exchange occurs through hydrogen bonding and π-π stacking interactions in 3. All complexes are proved to be efficient catalysts for the epoxidation of alkenes by NaOCl under phase transfer condition. The efficiency of alkene epoxidation is dramatically enhanced by lowering the pH, and the reactions are supposed to involve high valent Ni III-OCl or Ni III-O· intermediates. 3 is the best epoxidation catalyst among the three complexes with 99% conversion and very high turnover number (TON, 396). © 2011 American Chemical Society.